PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SD SWASTA RA KARTINI CERDAS BANGSA - Juita Afriliana Saragih; Rapita Silalahi, Beta; Nila Lestari; Nurjannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Problem Based Learning (PBL) model on the learning outcomes of IPAS for fourth-grade students at SD Swasta Ra Kartini Cerdas Bangsa. The background of this study is based on the low IPAS learning outcomes caused by teacher-centered learning, limited use of learning media, and low student participation during the learning process. This study employed a quantitative approach using a quasi-experimental method with a One-Group Pretest–Posttest design. The research subjects consisted of 23 fourth-grade students at SD Swasta Ra Kartini Cerdas Bangsa. Data were collected through learning outcome tests in the form of pretests and posttests. The results showed that the average pretest score was 80.00, while the average posttest score increased to 90.52, indicating an improvement of 10.52 points. The normality test results indicated that both pretest and posttest data were normally distributed. Furthermore, the results of the paired samples t-test showed a t-value of –11.989 with a significance value of 0.000 < 0.05, which indicates a significant difference between students’ learning outcomes before and after the implementation of the Problem Based Learning model. Therefore, it can be concluded that the Problem Based Learning model has a positive and significant effect on IPAS learning outcomes of fourth-grade students at SD Swasta Ra Kartini Cerdas Bangsa.